2001
DOI: 10.1097/00000539-200101000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Awake Craniotomy for Removal of Intracranial Tumor: Considerations for Early Discharge

Abstract: It may be feasible to perform awake craniotomies for removal of intracranial tumor as an ambulatory procedure; however, caution is advised. Patient selection must be stringent with respect to the patient's preoperative functional status, tumor depth, surrounding edema, patient support at home, and ease of access to hospital for readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 11 publications
6
103
0
5
Order By: Relevance
“…Dexmedetomidine is a highly specific In the United States, majority of these procedures are performed under local anaesthesia with sedation and it is considered as standard approach to certain supratentorial tumours [12]. A shorter hospital stay results in considerable cost reduction and some centres advocate day-case procedures [13]. The term conscious sedation has been used widely, however it is such an amorphous term that the term 'sedation and analgesia' is recommended [14].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a highly specific In the United States, majority of these procedures are performed under local anaesthesia with sedation and it is considered as standard approach to certain supratentorial tumours [12]. A shorter hospital stay results in considerable cost reduction and some centres advocate day-case procedures [13]. The term conscious sedation has been used widely, however it is such an amorphous term that the term 'sedation and analgesia' is recommended [14].…”
Section: Discussionmentioning
confidence: 99%
“…Established exclusion criteria to awake craniotomy include patients unable to cooperate because of severe dysphasia, language barrier, cognitive impairment, emotional instability or delirium, as well as patients with low occipital tumors (requiring prone positioning) or tumors involving significant dural attachment (due to the probability of significant dural pain on resection). 4,7 It has further been recommended that patients under the age of 11 not be considered for awake craniotomy. 18 From the experience of the senior author, attention to these principles combined with experienced surgical and anesthesia teams who communicate well, results in smooth awake craniotomies in the overwhelming majority of cases with intraoperative problems significant enough to call into question whether awake craniotomy was the best choice for a particular patient occurring in approximately 1% of cases.…”
Section: Utilizationmentioning
confidence: 99%
“…Outpatient awake craniotomy has been demonstrated to maximize resource utilization and increase patient satisfaction. 7 Furthermore, it likely reduces the potential for infection, thromboembolic events, and other hospital-based complications. 29,30 Patients have reported that having brain surgery done as outpatients made their disease seem less serious, which contributed to emotional well-being and aided in the recovery process.…”
Section: Surgical Innovationmentioning
confidence: 99%
See 2 more Smart Citations